Effects of nitric oxide on sunflower seedlings: A balance between defense and development - Monzón, Georgina Corti (Plant Signal Behav, 2015)
Nitric oxide (NO) is a major plant signaling molecule that plays key roles during plant-pathogen interactions and plant development. Previous work showed the participation of NO in the development and lignin composition of sunflower roots. Thereby, we have hypothesized that NO applications could control the attack of the fungal pathogen Verticillium dahliae in sunflowers. Seedlings growing hydroponically were pretreated with NO donors and further inoculated with the fungus. Evaluation of disease symptoms showed that NO pretreatments could not reduce Verticillium wilt. Strikingly, NO donors appear to promote the fungal infection. These results indicate that NO applications were unable to protect sunflowers from Verticillium attack and highlight the role played by the fine tuning regulation of NO levels required to balance plant responses between development and defense.